Genomics Protocols - Starkey, Mike.; Starkey, Mike.; Elaswarapu, Ramnath.; Elaswarapu, Ramnath. (Methods in Molecular Biology,, 2008)
Since the first edition, published in 2001, genomics research has taken great strides. In Genomics Protocols, 2nd Edition, a team of expert researchers share the most current information in a field that has recently switched emphasis from gene identification to functional genomics and the characterization of genes and gene products. This volume approaches its complex subject with a broad perspective to supply its reader with a vital overview of genomics and its derivative fields, with a focus on pivotal issues such as data analysis. Following the highly successful Methods in Molecular Biology™ series format, the chapters provide easy-to-follow laboratory protocols, lists of the necessary materials, and the excellent Notes section, which offers tips on troubleshooting and avoiding known pitfalls. Expansive and current, Genomics Protocols, 2nd Edition is the perfect update for researchers working in this integral, growing field.